Sugammadex, the Guardian of Deep Muscle Relaxation During Conventional and Robot-Assisted Laparoscopic Surgery: A Narrative Review - Sun Y; Wu Z; Wang Q; Chen R; Sun S; Lin Y (Dove Medical Press, 2021)
Yan Sun,* Zhilin Wu,* Qi Wang,* Rui Chen, Shujun Sun, Yun Lin Department of Anesthesiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of China*These authors contributed equally to this workCorrespondence: Shujun Sun; Yun LinDepartment of Anesthesiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1277, Jiefang Avenue, Wuhan, 430022, People's Republic of ChinaTel/Fax +86 02785351606Email sunshunjun@foxmail.com; franklinyun@hust.edu.cnAbstract: High intra-abdominal pressure induced by artificial pneumoperitoneum can obviously impair respiratory and circulatory functions and has a negative effect on the prognosis of patients undergoing conventional and robot-assisted laparoscopic surgery. The application of deep neuromuscular blockade during the operation is reported to lower the intra-abdominal pressure and improve patients' outcome. However, concern lies in the risks of postoperative residual muscular paralysis with the use of deep neuromuscular blockade. Sugammadex, a specific antagonist for aminosteroids muscle relaxants, can effectively and rapidly reverse rocuronium and vecuronium induced neuromuscular blockade of different depths. Thus, sugammadex allows the ability to safeguard the application of deep neuromuscular blockade in laparoscopic operations and helps to alleviate the adverse complications associated with pneumoperitoneum. Here, we review the application of deep neuromuscular blockade in different laparoscopic surgeries and discuss the benefits and possible risks of sugammadex administration in the reversal of deep neuromuscular blockade in these operations.Keywords: deep neuromuscular blockade, laparoscopic surgery, muscle relaxation remnants, sugammadex